Data from: Heart rate during hyperphagia differs between two bear species ... - Fuchs, Boris; Yamazaki, Koji; Evans, Alina L.; Tsubota, Toshio; Koike, Shinsuke; Naganuma, Tomoko; Arnemo, Jon M. (Dryad, 2018)
Hyperphagia is a critical part of the yearly cycle of bears when they gain fat reserves before entering hibernation. We used heart rate as a proxy to compare the metabolic rate between the Asian black bear (Ursus thibetanus) in Japan and the Eurasian brown bear (Ursus arctos) in Sweden from summer in to hibernation. In the hyperphagic period, black bears feed on fat- and carbohydrate-rich hard masts whereas brown bears feed on sugar-rich berries. Availability of hard masts has quantitative and spatial annual fluctuations, which might require increased activity and result in intraspecific stress. Using generalized additive mixed models we analyze the differences in heart rate between the two species. Black bears had decreased heart rates during summer but had doubled heart rate values throughout the hyperphagic period compared to brown bears. This letter illustrates different physiological consequences of seasonal differences in food availability in two species of the same genus dealing with the same ... : Daily mean heart rate of three asian black bears and four brown bearsHeart rate from three, free-ranging, female Asian black bears from Ashio, Japan and from four, free-ranging, female brown bears from Dalarna, Sweden. Data starts in mid May and ends in December. Object_ID is the unique ID of the bears. HeartRate is the daily mean heart rate in bpm GMT_date is the date for the mean heart rate. DenningDay is the day of the year the bear entered hibernation. BodyMass is the mass of the bear in kg. PrDenDay is the time difference of the GMT_date to the DenningDay in days. Species indicates the bear species.yradDataHyperphagia.txt ...